Alkaline electrolyzed water composite diaphragm with double functional groups and preparation method and application of alkaline electrolyzed water composite diaphragm
By bifunctional modification of nanoceramic particles and combining them with the sulfonated polymer support layer, the problems of poor mechanical strength and poor airtightness of alkaline electrolytic composite membrane are solved, and the performance of separators with low surface resistance and good airtightness are achieved, and the application prospects are good in the field of hydrogen energy production.
Patent Information
- Application Number
- CN202411736388.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
The existing alkaline hydrolytic composite membranes have problems such as poor mechanical strength, easy falloff of inorganic particles, high surface resistance and poor airtightness.
By bifunctional modification of nanoceramic particles with aminosilane coupling agent and sulfhydrylsilane coupling agent, combining with the sulfonated polymer support layer, forming a cast film liquid and coating to form a film, the tight bond between nanoceramic particles and organic polymer is achieved, and the mechanical properties and airtightness of the membrane are improved.
It improves the mechanical properties and performance stability of the composite diaphragm, reduces surface resistance, enhances airtightness, and extends the service life of the diaphragm.
Smart Images

Figure BDA0005161596240000121 
Figure BDA0005161596240000122 
Figure BDA0005161596240000131
Abstract
Description
Technical Field
[0001] The invention belongs to the field of alkaline water electrolysis hydrogen production, and specifically relates to a dual-functional alkaline water electrolysis composite diaphragm and a preparation method and application thereof. Background Art
[0002] The hydrogen energy industry is a strategic emerging industry and a key development direction for future industries. It is gradually becoming one of the important carriers of global energy transformation and development. At present, the mainstream commercial technologies for hydrogen production by water electrolysis include alkaline electrolysis and proton exchange membrane (PEM) electrolysis. Alkaline water electrolysis is the most widely used and most promising hydrogen production method in the world. The scale of a single device can reach 1000Nm 3 / h or more, and the cost is relatively low. At present, the market share of alkaline hydrogen production equipment accounts for more than 95% of domestic water electrolysis hydrogen production projects. As one of the most core materials for alkaline hydrogen production, the diaphragm plays an important role in conducting hydroxide ions and isolating the hydrogen produced by the cathode and the oxygen produced by the anode in the alkaline electrolyzer.
[0003] The commercial alkaline hydrogen production diaphragm has gone through three generations of development. The first generation is the asbestos diaphragm, which has been eliminated due to its high swelling and carcinogenicity; the second generation is the polyphenylene sulfide (PPS) diaphragm, which is currently the mainstream application; the third generation is the composite diaphragm, which is emerging and is generally considered to be the future development trend of the industry. Most of the short-filament PPS diaphragms on the market have the disadvantages of poor hydrophilicity, high resistance, and poor gas barrier properties, resulting in high energy consumption and low safety in water electrolysis. Therefore, compared with the short-filament PPS diaphragm, the alkaline water electrolysis composite diaphragm is favored by the industry due to its low surface resistance (reduced energy consumption) and high bubble point pressure (improved gas barrier properties).
[0004] Alkaline water electrolysis composite membranes are usually composed of a porous polymer support layer (such as PPS mesh) and an organic-inorganic hybrid hydrophilic layer, wherein the organic-inorganic hybrid hydrophilic layer includes an organic polymer substrate and an inorganic hydrophilic oxide. At present, most of the water electrolysis composite membranes have the following main problems: (1) Although the composite membrane has better gas barrier properties than the traditional PPS membrane, the membrane still has low hydrophilicity, high resistance and high energy consumption due to the hydrophobicity of the organic polymer; (2) Many composite membranes reported in the literature do not have a support mesh, and the mechanical strength of the membrane is low, making it difficult to apply industrially; (3) Due to the weak physical bonding between the inorganic particles and the polymer, it is easy to fall off during use (i.e., "powdering"), and the shedding of inorganic particles will affect the hydrogen production efficiency and the service life of the membrane; (4) The inorganic hydrophilic material used to prepare the composite membrane is single, easy to agglomerate, and has a high unit price, which increases the preparation cost. Summary of the invention
[0005] The purpose of the present invention is to provide a dual-functional alkaline water electrolysis composite diaphragm and its preparation method and application in view of the shortcomings of the existing alkaline water electrolysis composite diaphragm, such as poor mechanical strength, easy shedding of inorganic particles, high surface resistance and poor air tightness. The composite diaphragm has good mechanical properties, and the inorganic particles are tightly combined with the support layer material and are not easy to fall off. The composite diaphragm has stable performance, low surface resistance and good air tightness, and is expected to achieve good application prospects in the field of hydrogen energy production.
[0006] In a first aspect, the present invention provides a method for preparing a bifunctional alkaline water electrolysis composite membrane, the preparation method comprising the following steps: S1. mixing nano-ceramic particles with a modifying liquid and then performing a modification reaction, the modifying liquid containing an aminosilane coupling agent and a mercaptosilane coupling agent, to obtain amino- and mercapto-bifunctional modified nano-ceramic particles; placing a polymer support layer in a sulfonation liquid for a sulfonation modification reaction, the sulfonation liquid containing a sulfonic acid source compound, to obtain a sulfonated polymer support layer; S2. mixing the amino- and mercapto-bifunctional modified nano-ceramic particles, a polymer, a pore-forming agent, and a first organic solvent to obtain a casting liquid, degassing the casting liquid and coating it on the sulfonated polymer support layer to form a film, immersing the obtained composite membrane precursor in a coagulation bath for phase inversion, to obtain a bifunctional alkaline water electrolysis composite membrane.
[0007] In a preferred embodiment, the mass ratio of the nano-ceramic particles to the sum of the aminosilane coupling agent and the mercaptosilane coupling agent is 1:(0.05-1).
[0008] In a preferred embodiment, the volume ratio of the aminosilane coupling agent to the mercaptosilane coupling agent is 1:(0.5-2).
[0009] In a preferred embodiment, the modified liquid further contains a second organic solvent.
[0010] In a preferred embodiment, the second organic solvent is selected from at least one of methanol, toluene, diethyl ether, tetrahydrofuran and chloroform.
[0011] In a preferred embodiment, the particle size of the nano-ceramic particles is 20-100 nm.
[0012] In a preferred embodiment, the nano-ceramic particles contain nano-ceramic particles A and nano-ceramic particles B at the same time.
[0013] In a preferred embodiment, the nano-ceramic particles A and the nano-ceramic particles B are each independently selected from at least one of zirconium oxide, silicon oxide, zinc oxide, titanium oxide, calcium oxide, and aluminum oxide.
[0014] In a preferred embodiment, the mass ratio of the nano-ceramic particles A to the nano-ceramic particles B is 1:(0.5-5).
[0015] In a preferred embodiment, the sulfonation rate of the sulfonated polymer support layer is 0.5-10%.
[0016] In a preferred embodiment, the polymer in the sulfonated compound support layer is selected from at least one of polyphenylene sulfide, polypropylene, polysulfone, polyetheretherketone, polytetrafluoroethylene, and polyethylene.
[0017] In a preferred embodiment, the pore size of the sulfonated polymer support layer is 20-150 meshes.
[0018] In a preferred embodiment, the sulfonic acid source compound is selected from at least one of sulfuric acid, sodium dodecyl sulfate, chlorosulfonic acid, and aminosulfonic acid.
[0019] In a preferred embodiment, the sulfonation liquid is concentrated sulfuric acid.
[0020] In a preferred embodiment, the ratio of the polymer support layer to concentrated sulfuric acid is 1 cm 2 :(1~6)mL.
[0021] In a preferred embodiment, based on the total mass of the casting solution, the content of the bifunctional modified nano-ceramic particles is 30-65wt%, the content of the polymer is 6-25wt%, the content of the pore-forming agent is 3-15wt%, and the content of the first organic solvent is 20-45wt%.
[0022] In a preferred embodiment, the polymer is selected from at least one of polysulfone, polyethersulfone, polyphenylene sulfide, polytetrafluoroethylene, polyphenylsulfone and polypropylene.
[0023] In a preferred embodiment, the pore-forming agent is selected from at least one of polyvinyl pyrrolidone, polyethylene glycol, glycerol and polyvinyl alcohol.
[0024] In a preferred embodiment, the second organic solvent is selected from at least one of N-methylpyrrolidone, dimethyl sulfoxide, dimethylformamide, and dimethylacetamide.
[0025] In a preferred embodiment, the coagulation bath is deionized water.
[0026] In a preferred embodiment, the modification reaction conditions include: temperature of 30 to 80° C. and time of 16 to 24 hours.
[0027] In a preferred embodiment, the conditions of the sulfonation reaction include: temperature of 40-70° C. and time of 0.5-2 h.
[0028] In a preferred embodiment, the degassing treatment method is selected from at least one of ultrasonic degassing, centrifugal degassing and vacuum degassing.
[0029] In a preferred embodiment, the degassing treatment time is 0.5 to 5 hours.
[0030] In a preferred embodiment, the phase inversion conditions include: temperature of 5 to 40° C. and time of 15 to 40 min.
[0031] In a second aspect, the present invention provides a bifunctional alkaline water electrolysis composite diaphragm prepared by the above method.
[0032] In a third aspect, the present invention also provides the application of the above-mentioned bifunctional alkaline water electrolysis composite membrane in the field of alkaline water electrolysis hydrogen production.
[0033] The key to the present invention is to perform bifunctional modification on nano-ceramic particles by amino and thiol groups, and the obtained bifunctional modified nano-ceramic particles are combined with polymer materials to obtain a casting solution, which is then composited with a sulfonated polymer support layer. On the one hand, the presence of amino, thiol and sulfonyl groups can improve the hydrophilicity of the composite membrane and promote the OH in the electrolyte. - The conduction rate is increased, which is beneficial to reduce the surface resistance of the composite diaphragm. On the other hand, the amino and thiol groups of the bifunctional modified nano-ceramic particles can produce chemical cross-linking with the sulfonate groups of the sulfonated polymer support layer, so that the nano-ceramic particles are tightly combined with the organic polymer support layer, and the nano-ceramic particles are not easy to fall off during the application process, thereby enhancing the mechanical strength and performance stability of the composite diaphragm and extending the service life of the diaphragm. At the same time, the presence of amino, thiol and sulfonate groups is beneficial to enhancing the delayed phase separation during the formation of the composite diaphragm, forming a dense membrane structure, thereby improving the air tightness of the composite diaphragm. In summary, the bifunctional alkaline water electrolysis composite diaphragm provided by the present invention has good mechanical properties, stable performance, low surface resistance, and good air tightness, and is expected to achieve good application prospects in the field of hydrogen energy production. DETAILED DESCRIPTION
[0034] In order to make the technical personnel better understand the scheme of the present invention, the present invention is further described in detail below in conjunction with specific embodiments. The following examples are for better understanding of the present invention, but are not to be construed as limiting the present invention. The chemical reagents and materials in the present invention are purchased through market channels or synthesized from raw materials purchased through market channels, and the equipment used is equipment commonly used in the art. The experimental methods in the following examples, unless otherwise specified, are conventional methods in the art.
[0035] The preparation method of the bifunctional alkaline water electrolysis composite diaphragm provided by the present invention comprises the following steps: S1. mixing nano ceramic particles with a modifying liquid and then performing a modification reaction, wherein the modifying liquid contains an aminosilane coupling agent and a mercaptosilane coupling agent, so as to obtain amino and mercapto bifunctional modified nano ceramic particles; placing a polymer support layer in a sulfonation liquid for a sulfonation modification reaction, wherein the sulfonation liquid contains a sulfonic acid source compound, so as to obtain a sulfonated polymer support layer; S2. mixing the amino and mercapto bifunctional modified nano ceramic particles, a polymer, a pore-forming agent, and a first organic solvent to obtain a casting liquid, degassing the casting liquid and coating it on the sulfonated polymer support layer to form a film, immersing the obtained composite diaphragm precursor in a coagulation bath for phase conversion, so as to obtain a bifunctional alkaline water electrolysis composite diaphragm.
[0036] In the present invention, the mass ratio of the nano-ceramic particles to the sum of the aminosilane coupling agent and the mercaptosilane coupling agent is preferably 1:(0.05-1), such as 1:0.05, 1:0.1, 1:0.2, 1:0.5, 1:0.8, 1:1 or any value therebetween. The volume ratio of the aminosilane coupling agent to the mercaptosilane coupling agent is preferably 1:(0.5-2), such as 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2 or any value therebetween. The modified liquid may be a liquid containing only the aminosilane coupling agent and the mercaptosilane coupling agent, or a liquid containing the aminosilane coupling agent, the mercaptosilane coupling agent and the second organic solvent. The modified liquid of the present invention is preferably the latter. The presence of the second organic solvent can provide a favorable reaction environment for the modification reaction between the nano-ceramic particles and the aminosilane coupling agent and the mercaptosilane coupling agent. The volume ratio of the sum of the aminosilane coupling agent and the mercaptosilane coupling agent to the second organic solvent is preferably 1:(20-100), such as 1:20, 1:30, 1:50, 1:60, 1:80, 1:90, 1:100 or any value therebetween. In addition, "first" and "second" are only used to refer to the organic solvents that appear in sequence during the preparation process for easy distinction, and cannot be understood as a special limitation on the type of organic solvent.
[0037] In a specific embodiment, the step S1 can be carried out as follows: after the nano-ceramic particles and the modified liquid are uniformly mixed by ultrasonic, a modification reaction is carried out under an inert gas atmosphere, and the product after the reaction is washed and dried to obtain the bifunctional modified nano-ceramic particles. The purpose of the ultrasonic mixing is to make the nano-ceramic particles dispersed uniformly in the modified liquid. The present invention does not specifically limit the conditions of the ultrasonic mixing. The conditions of the ultrasonic mixing may include: the temperature is preferably 15 to 30°C, such as 15°C, 18°C, 20°C, 22°C, 25°C, 30°C or any value therebetween; the time is preferably 0.5 to 1h, such as 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h or any value therebetween. The inert gas is preferably at least one of nitrogen, argon, xenon, helium, and radon, and more preferably nitrogen and / or argon. The purpose of the washing is to remove unreacted aminosilane coupling agent and mercaptosilane coupling agent, and the specific steps are as follows: the obtained product is washed with a second organic solvent and ethanol in sequence.
[0038] In the present invention, the particle size of the nano ceramic particles is preferably 20 to 100 nm, such as 20 nm, 50 nm, 80 nm, 100 nm or any value therebetween. The nano ceramic particles of the present invention may contain only one nano ceramic particle, or may contain two or more different ceramic nano particles, preferably containing nano ceramic particles A and nano ceramic particles B at the same time. At this time, the composite nano ceramic particles containing nano ceramic particles A and nano ceramic particles B at the same time are more conducive to overcoming the problem of easy agglomeration of single nano ceramic particles, improving the uniformity and flatness of the composite diaphragm, and the composite nano ceramic particles are also more conducive to improving the hydrophilicity, thereby reducing the surface resistance of the composite diaphragm. The nano ceramic particles A and nano ceramic particles B can each independently be selected from at least one of zirconium oxide, silicon oxide, zinc oxide, titanium oxide, calcium oxide, and aluminum oxide. More preferably, the nano ceramic particles A can be zirconium oxide, and the nano ceramic particles B can be selected from at least one of silicon oxide, zinc oxide, titanium oxide, calcium oxide, and aluminum oxide. When this specific form is used in combination, it is more conducive to reducing the surface resistivity of the composite diaphragm.
[0039] The mass ratio of the nano-ceramic particles A to the nano-ceramic particles B is preferably 1:(0.5-5), such as 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5 or any value therebetween.
[0040] In the present invention, the sulfonation rate of the sulfonated polymer support layer is preferably 0.5-10%, such as 0.5%, 1%, 2%, 5%, 8%, 10% or any value therebetween. Specific examples of the polymer in the sulfonated compound support layer include, but are not limited to, at least one of polyphenylene sulfide, polypropylene, polysulfone, polyetheretherketone, polytetrafluoroethylene, and polyethylene. The pore size of the sulfonated polymer support layer is preferably 20-150 mesh, such as 20 mesh, 50 mesh, 80 mesh, 100 mesh, 120 mesh, 150 mesh or any value therebetween. The thickness of the sulfonated polymer support layer is preferably 80-300 μm, such as 80 μm, 100 μm, 125 μm, 150 μm, 175 μm, 200 μm, 250 μm, 300 μm or any value therebetween.
[0041] In the present invention, the sulfonic acid source compound can be any compound that can provide sulfonic acid groups in the sulfonation modification reaction, and specific examples thereof include but are not limited to at least one of sulfuric acid, sodium dodecyl sulfate, chlorosulfonic acid, and aminosulfonic acid. The sulfonation liquid is preferably concentrated sulfuric acid, which is more conducive to modifying the sulfonic acid groups on the polymer support layer in the sulfonation reaction. The ratio of the polymer support layer to the concentrated sulfuric acid is preferably 1 cm 2 :(1~6)mL, such as 1cm 2 :1mL、1cm 2 :2mL、1cm 2 :2mL、1cm 2 :4mL、1cm 2 :5mL, 1cm 2 :6mL or any value in between.
[0042] In the present invention, based on the total mass of the casting solution, the content of the bifunctional modified nano-ceramic particles is preferably 30-65wt%, such as 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt% or any value therebetween; the content of the polymer is preferably 6-25wt%, such as 6wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, 22wt%, 25wt% or any value therebetween; the content of the pore-forming agent is preferably 3-15wt%, such as 3wt%, 5wt%, 8wt%, 10wt%, 12wt%, 15wt% or any value therebetween; the content of the first organic solvent is preferably 20-45wt%, such as 20wt%, 25wt%, 30wt%, 32wt%, 35wt%, 38wt%, 40wt%, 42wt%, 45wt% or any value therebetween.
[0043] In the present invention, in step S3, the mixing method and order of the bifunctional modified nano ceramic particles, polymer, pore-forming agent, and first organic solvent can be adjusted according to actual conditions. In a specific embodiment, step S3 can be performed as follows: dissolve the polymer in the first organic solvent, add the pore-forming agent and mix evenly, then continue to add the bifunctional modified nano ceramic particles and mix evenly to obtain a casting liquid, degas the casting liquid and evenly coat it on the sulfonated polymer support layer, then use a film scraping machine to scrape the film, immerse the evenly coated composite diaphragm precursor in a coagulation bath for phase inversion, and obtain a bifunctional alkaline electrolysis water composite diaphragm. In addition, before the phase inversion, the composite diaphragm precursor can also be placed in the air for static treatment, and the static treatment time is preferably 10 to 100 seconds, such as 10 seconds, 20 seconds, 50 seconds, 80 seconds, 100 seconds or any value therebetween. After the phase inversion, a soaking and cleaning treatment may be further included, that is, the composite membrane after the phase inversion is soaked and cleaned with pure water for 2 to 4 times until the water is transparent and colorless, thereby obtaining a bifunctional alkaline water electrolysis composite membrane.
[0044] In the present invention, the polymer is mainly used as a film-forming resin. The polymer is preferably selected from at least one of polysulfone, polyethersulfone, polyphenylene sulfide, polytetrafluoroethylene, polyphenylsulfone, and polypropylene, and more preferably at least one of polysulfone, polyethersulfone, and polyphenylsulfone. At this time, the amino group and the sulfhydryl group on the bifunctional modified nano-ceramic particles can produce chemical crosslinking with the sulfone group on the polysulfone and / or polyethersulfone and / or polyphenylsulfone, which is more conducive to the uniform dispersion of the nano-ceramic particles in the polymer and close combination, enhancing the mechanical strength and stability of the composite diaphragm, and also making the surface of the composite diaphragm more flat and uniform. In addition, the weight average molecular weight Mw of the polymer is preferably 50000-100000 g / mol, such as 50000 g / mol, 60000 g / mol, 70000 g / mol, 80000 g / mol, 90000 g / mol, 100000 g / mol or any value therebetween.
[0045] In the present invention, the function of the pore-forming agent is to introduce a pore structure into the polymer, which is conducive to the composite between the polymer and the bifunctional modified nano-ceramic particles. Specific examples thereof include, but are not limited to, at least one of polyvinyl pyrrolidone, polyethylene glycol, glycerol, and polyvinyl alcohol, and more preferably polyvinyl pyrrolidone K90 and / or polyethylene glycol. The presence of the second organic solvent enables the bifunctional modified nano-ceramic particles, the polymer, and the pore-forming agent to be uniformly mixed, which facilitates the subsequent coating of the casting solution on the sulfonated polymer support layer to form a film. Specific examples thereof include, but are not limited to, at least one of N-methylpyrrolidone, dimethyl sulfoxide, dimethylformamide, and dimethylacetamide, and more preferably N-methylpyrrolidone and / or dimethyl sulfoxide. The coagulation bath is preferably deionized water.
[0046] In the present invention, the conditions of the modification reaction specifically include: the temperature is preferably 30-80°C, such as 30°C, 40°C, 50°C, 60°C, 70°C, 80°C or any value therebetween; the time is preferably 16-24h, such as 16h, 18h, 20h, 22h, 24h or any value therebetween.
[0047] In the present invention, the conditions of the sulfonation reaction specifically include: the temperature is preferably 40-70°C, such as 40°C, 50°C, 60°C, 70°C or any value therebetween; the time is preferably 0.5-2h, such as 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h or any value therebetween.
[0048] In the present invention, the degassing treatment is preferably at least one of ultrasonic degassing, centrifugal degassing and vacuum degassing. The degassing treatment time is preferably 0.5 to 5 hours, such as 0.5 hours, 0.8 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or any value therebetween.
[0049] In the present invention, the conditions for phase inversion specifically include: the temperature is preferably 5-40°C, such as 5°C, 10°C, 20°C, 30°C, 40°C or any value therebetween; the time is preferably 15-40min, such as 15min, 20min, 25min, 30min, 35min, 40min or any value therebetween.
[0050] In the present invention, the thickness of the bifunctional alkaline water electrolysis composite membrane is preferably 350-650 μm, such as 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 650 μm or any value therebetween.
[0051] The present invention will be described in detail below through specific embodiments.
[0052] Example 1
[0053] (1) Dual-functional modification of composite nano-ceramic particles: 30 g ZrO2 and 30 g TiO2 with a particle size of 80 nm were weighed and added to 412 mL of modification solution (400 mL toluene, 5.33 mL 3-aminopropylmethyldiethoxysilane and 6.67 mL 3-mercaptopropyltrimethoxysilane), and then dispersed evenly by ultrasonication at 26°C for 30 min. Then, the particles were magnetically stirred in an oil bath at 60°C for 18 h in a 0.4 L / min N2 atmosphere to carry out the modification reaction. After the reaction, the product was washed three times with a toluene solution to remove the unreacted silane coupling agent, and then washed twice with anhydrous ethanol to remove the toluene solvent. The washed product was placed in a vacuum drying oven at 80°C for 10 h and then stored to obtain amino- and mercapto-dual-functional modified nano ZrO2-TiO2.
[0054] (2) Sulfonation of polymer support layer: a 10 cm × 10 cm 40 mesh 250 μm thick polyphenylene sulfide mesh support layer was immersed in 120 mL of concentrated sulfuric acid (concentration: 98.3%) and reacted at 60° C. for 1 h. The support layer was taken out and soaked in a 1 mol / L KOH aqueous solution for 10 min. The support layer was then washed with deionized water until the pH value was neutral and then dried to obtain a sulfonated polyphenylene sulfide mesh support layer with a sulfonation rate of 1.76%.
[0055] (3) preparing a casting solution: dissolving 10 g of polysulfone (98%, purchased from MacLean Chemical Reagent Co., Ltd., brand P856835, weight average molecular weight 80,000 g / mol) in 32 g of N-methylpyrrolidone, adding 3 g of polyvinylpyrrolidone K90 when the polymer is completely dissolved, stirring evenly, adding 50 g of amino- and thiol-bifunctional modified nano ZrO2-TiO2, and then continuing to stir at room temperature until a uniform casting solution is obtained;
[0056] (4) Degassing coating: After the casting solution is ultrasonically degassed for 0.5 h, it is evenly coated on a sulfonated polyphenylene sulfide mesh support layer placed on a glass plate, the height between the scraper and the glass plate is adjusted to 500 μm, and a film is scraped using a film scraping machine to obtain a composite diaphragm precursor;
[0057] (5) Pre-evaporation: let the evenly coated composite membrane precursor stand in air for 30 seconds;
[0058] (6) Immersion precipitation phase transformation: The pre-evaporated composite membrane precursor was placed in deionized water at 25 °C for 30 min;
[0059] (7) Post-treatment: The phase-converted diaphragm is soaked and cleaned with deionized water for three times until the water becomes transparent and colorless, thereby obtaining a bifunctional alkaline water electrolysis composite diaphragm.
[0060] Example 2
[0061] A bifunctional alkaline water electrolysis composite membrane was prepared according to the method of Example 1, except that in step (1), 412 mL of modifying liquid (400 mL of toluene, 8.00 mL of 3-aminopropylmethyldiethoxysilane and 4.00 mL of 3-mercaptopropyltrimethoxysilane) was used instead of 412 mL of modifying liquid (400 mL of toluene, 5.33 mL of 3-aminopropylmethyldiethoxysilane and 6.67 mL of 3-mercaptopropyltrimethoxysilane), and the other conditions were the same as in Example 1, thereby preparing a bifunctional alkaline water electrolysis composite membrane.
[0062] Example 3
[0063] A bifunctional alkaline water electrolysis composite membrane was prepared according to the method of Example 1, except that in step (1), 412 mL of modifying liquid (400 mL of toluene, 4.00 mL of 3-aminopropylmethyldiethoxysilane and 8.00 mL of 3-mercaptopropyltrimethoxysilane) was used instead of 412 mL of modifying liquid (400 mL of toluene, 5.33 mL of 3-aminopropylmethyldiethoxysilane and 6.67 mL of 3-mercaptopropyltrimethoxysilane), and the other conditions were the same as in Example 1, thereby preparing a bifunctional alkaline water electrolysis composite membrane.
[0064] Example 4
[0065] A bifunctional alkaline water electrolysis composite membrane was prepared according to the method of Example 1, except that in step (3): 15 g of polysulfone was dissolved in 37 g of N-methylpyrrolidone, and 3 g of polyvinylpyrrolidone K90 was added when the polymer was completely dissolved. After stirring evenly, 40 g of amino and thiol bifunctional modified nano ZrO2-TiO2 was added, and then stirring was continued at room temperature until a uniform casting solution was obtained. The remaining conditions were the same as in Example 1, thereby preparing a bifunctional alkaline water electrolysis composite membrane.
[0066] Example 5
[0067] A bifunctional alkaline water electrolysis composite membrane was prepared according to the method of Example 1, except that in step (3): 13 g of polysulfone was dissolved in 32 g of N-methylpyrrolidone, and 3 g of polyvinylpyrrolidone K90 was added when the polymer was completely dissolved. After stirring evenly, 45 g of amino and thiol bifunctional group-modified nano ZrO2-TiO2 was added, and then stirring was continued at room temperature until a uniform casting solution was obtained; the other conditions were the same, thereby preparing a bifunctional alkaline water electrolysis composite membrane.
[0068] Example 6
[0069] A bifunctional alkaline water electrolysis composite membrane was prepared according to the method of Example 1, except that the same mass of ZrO2 was used instead of TiO2, and the other conditions were the same, thereby preparing a bifunctional alkaline water electrolysis composite membrane.
[0070] Example 7
[0071] A bifunctional alkaline water electrolysis composite membrane was prepared according to the method of Example 1, except that TiO2 of the same mass was used instead of ZrO2, and the other conditions were the same, thereby preparing a bifunctional alkaline water electrolysis composite membrane.
[0072] Example 8
[0073] A bifunctional alkaline water electrolysis composite membrane was prepared according to the method of Example 1, except that the same mass of polyphenylsulfone (purchased from McLean Chemical Reagent Co., Ltd., brand P776216, weight average molecular weight 80000 g / mol) was used instead of polysulfone, and the other conditions were the same, thereby preparing a bifunctional alkaline water electrolysis composite membrane.
[0074] Comparative Example 1
[0075] A reference alkaline water electrolysis composite membrane was prepared according to the method of Example 1, except that 12 mL of 3-aminopropylmethyldiethoxysilane was used instead of 5.33 mL of 3-aminopropylmethyldiethoxysilane and 6.67 mL of 3-mercaptopropyltrimethoxysilane, and the other conditions were the same, thereby preparing a reference alkaline water electrolysis composite membrane.
[0076] Comparative Example 2
[0077] A reference alkaline water electrolysis composite membrane was prepared according to the method of Example 1, except that 12 mL of 3-mercaptopropyltrimethoxysilane was used instead of 5.33 mL of 3-aminopropylmethyldiethoxysilane and 6.67 mL of 3-mercaptopropyltrimethoxysilane, and the other conditions were the same, thereby preparing a reference alkaline water electrolysis composite membrane.
[0078] Comparative Example 3
[0079] A reference alkaline water electrolysis composite membrane was prepared according to the method of Example 1, except that the polyphenylene sulfide mesh support layer was not sulfonated and the other conditions were the same, thereby preparing a reference alkaline water electrolysis composite membrane.
[0080] Comparative Example 4
[0081] A reference alkaline water electrolysis composite membrane was prepared according to the method of Example 1, except that the composite nano-ceramic particles were not modified, and other conditions were the same, thereby preparing a reference alkaline water electrolysis composite membrane.
[0082] Comparative Example 5
[0083] A purchased commercial Zirfon PERL UTP 500 alkaline water electrolysis composite membrane.
[0084] Test Case
[0085] (1) The alkaline water electrolysis composite diaphragm prepared in the above examples and comparative examples was clamped in an electrolysis chamber, with purchased nickel mesh as anode and cathode, 30 wt % KOH as electrolyte, and tested in an 80 ° C oil bath pot, and an external DC power supply was connected to control the current density to 0.4 A / cm 2 , 0.6A / cm 2 , 0.8A / cm 2 , 1.0A / cm 2 , the electrode voltage (V) under the above current density was tested in turn using a multimeter, and the test results are shown in Table 1 below.
[0086] Table 1
[0087]
[0088] It can be seen from the test results in Table 1 that, at the same current density, the voltage required for Examples 1 to 8 is less than that for Comparative Examples 1 to 5, indicating that the alkaline water electrolysis composite diaphragm prepared by the present invention has a smaller surface resistance and a stronger conductivity, and less energy consumption is required in actual water electrolysis to produce hydrogen.
[0089] (2) The thickness, contact angle, alkali loss, tensile strength, surface resistance and bubble point pressure of the alkaline water electrolysis composite membrane prepared in the above examples and comparative examples were measured. The thickness, alkali loss and surface resistance test methods refer to SJ / T10171.5-2016 "Alkaline Battery Diaphragm Performance Test Method", and other properties were tested using conventional methods and instruments. The results are shown in Table 2.
[0090] Table 2
[0091]
[0092]
[0093] From the results of Table 2, it can be seen that the composite membranes obtained in Examples 1 to 8 have lower alkali loss and higher tensile strength and bubble point pressure, indicating that the composite membrane has stable performance, high mechanical strength, good air tightness, and has the characteristics of good hydrophilicity, high porosity, and low surface resistance. From the results of Example 1 and Comparative Example 1, Comparative Example 2, and Comparative Example 4, it can be seen that compared with nano-ceramic particles with single amino or thiol modification, or unmodified nano-ceramic particles, the composite membrane with amino and thiol bifunctional groups has better comprehensive performance. From the results of Example 1 and Comparative Example 3, it can be seen that compared with the use of a polymer support layer that has not been sulfonated, the bifunctional alkaline water electrolysis composite membrane provided in the embodiment has higher hydrophilicity, porosity, tensile strength and bubble point pressure and low surface resistance, and the composite membrane has stable performance, high mechanical strength, and good air tightness. From the results of Example 1 and Comparative Example 5, it can be seen that compared with the existing commercial alkaline water electrolysis composite membrane, the bifunctional base alkaline water electrolysis composite membrane provided in Example 1 has higher hydrophilicity, porosity, tensile strength and bubble point pressure and low surface resistance, and the composite membrane has stable performance, high mechanical strength and good air tightness. And the surface resistance data of Examples 1 to 8 and Comparative Examples 1 to 5 are consistent with the data results of voltage tests at different current densities.
[0094] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A method for preparing a bifunctional alkaline water electrolysis composite membrane, characterized in that: The preparation method comprises the following steps: S1. The nano-ceramic particles are mixed with a modification liquid and subjected to a modification reaction, wherein the modification liquid contains an aminosilane coupling agent and a mercaptosilane coupling agent to obtain amino- and mercapto-bifunctional modified nano-ceramic particles; the polymer support layer is placed in a sulfonation liquid for a sulfonation modification reaction, wherein the sulfonation liquid contains a sulfonic acid source compound to obtain a sulfonated polymer support layer; S2. The amino and thiol bifunctional modified nano-ceramic particles, polymer, pore-forming agent and first organic solvent are mixed to obtain a casting solution, which is degassed and coated on a sulfonated polymer support layer to form a film. The obtained composite membrane precursor is immersed in a coagulation bath for phase transformation to obtain a bifunctional alkaline water electrolysis composite membrane.
2. The method for preparing a bifunctional alkaline water electrolysis composite membrane according to claim 1, characterized in that: The mass ratio of the nano-ceramic particles to the sum of the aminosilane coupling agent and the mercaptosilane coupling agent is 1:(0.05-1); Preferably, the volume ratio of the aminosilane coupling agent to the mercaptosilane coupling agent is 1:(0.5-2); Preferably, the modified liquid further contains a second organic solvent; Preferably, the second organic solvent is selected from at least one of methanol, toluene, diethyl ether, tetrahydrofuran and chloroform.
3. The method for preparing a bifunctional alkaline water electrolysis composite membrane according to claim 1, characterized in that: The particle size of the nano ceramic particles is 20 to 100 nm; Preferably, the nano-ceramic particles contain both nano-ceramic particles A and nano-ceramic particles B; Preferably, the nano-ceramic particles A and the nano-ceramic particles B are each independently selected from at least one of zirconium oxide, silicon oxide, zinc oxide, titanium oxide, calcium oxide, and aluminum oxide; Preferably, the mass ratio of the nano-ceramic particles A to the nano-ceramic particles B is 1:(0.5-5).
4. The method for preparing a bifunctional alkaline water electrolysis composite membrane according to claim 1, characterized in that: The sulfonation rate of the sulfonated polymer support layer is 0.5 to 10%; Preferably, the polymer in the sulfonated compound support layer is selected from at least one of polyphenylene sulfide, polypropylene, polysulfone, polyetheretherketone, polytetrafluoroethylene, and polyethylene; Preferably, the pore size of the sulfonated polymer support layer is 20-150 meshes.
5. The method for preparing a bifunctional alkaline water electrolysis composite membrane according to claim 1, characterized in that: The sulfonic acid source compound is selected from at least one of sulfuric acid, sodium dodecyl sulfonate, chlorosulfonic acid, and aminosulfonic acid; preferably, the sulfonation liquid is concentrated sulfuric acid; Preferably, the ratio of the polymer support layer to concentrated sulfuric acid is 1 cm 2 :(1~6)mL.
6. The method for preparing a bifunctional alkaline water electrolysis composite membrane according to claim 1, characterized in that: Based on the total mass of the casting solution, the content of the bifunctional modified nano-ceramic particles is 30-65wt%, the content of the polymer is 6-25wt%, the content of the pore-forming agent is 3-15wt%, and the content of the first organic solvent is 20-45wt%.
7. The method for preparing a bifunctional alkaline water electrolysis composite membrane according to claim 1, characterized in that: The polymer is selected from at least one of polysulfone, polyethersulfone, polyphenylene sulfide, polytetrafluoroethylene, polyphenylsulfone, and polypropylene; Preferably, the pore-forming agent is selected from at least one of polyvinyl pyrrolidone, polyethylene glycol, glycerol, and polyvinyl alcohol; Preferably, the second organic solvent is selected from at least one of N-methylpyrrolidone, dimethyl sulfoxide, dimethylformamide, and dimethylacetamide; Preferably, the coagulation bath is deionized water.
8. The method for preparing a bifunctional alkaline water electrolysis composite membrane according to claim 1, characterized in that: The modification reaction conditions include: temperature of 30 to 80°C and time of 16 to 24 hours; Preferably, the conditions of the sulfonation reaction include: temperature of 40 to 70° C., time of 0.5 to 2 h; Preferably, the degassing treatment method is selected from at least one of ultrasonic degassing, centrifugal degassing and vacuum degassing; Preferably, the degassing treatment time is 0.5 to 5 hours; Preferably, the phase inversion conditions include: temperature of 5 to 40° C. and time of 15 to 40 min.
9. A bifunctional alkaline water electrolysis composite diaphragm prepared by the method according to any one of claims 1 to 8.
10. Application of the bifunctional alkaline water electrolysis composite diaphragm according to claim 9 in the field of alkaline water electrolysis hydrogen production.
Citation Information
Cited By
Preparation method of functional composite diaphragm
CN121381075A
Preparation method of functional composite diaphragm
CN121381075B